Catalytic Conversion of Energy Resources into High Value-Added Products - Pinilla, José Luis; Suelves, Isabel; García, Tomás (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Developing active, selective and energy-efficient heterogeneous catalysts is of paramount importance for the production of high value-added products from energy resources in a more sustainable manner. In this Special Issue of Energies, we provide a showcase of the latest progress in the development of cleaner, more efficient processes for the conversion of these feedstocks into valuable fuels, chemicals and energy. Most of the works collected are focused on the conversion of biomass which clearly reflects the paramount importance that the biorefinery concept will play in the years to come.